Pengaruh Pertumbuhan Ekonomi, Kemiskinan, Dan Belanja Daerah Terhadap Indeks Pembangunan Manusia Di Kabupaten Kota Provinsi Bali Periode 2005 – 2013 - Nedo, Adelfina; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
In economic paradigm, there has been changing in measuring rod of economic succeed from economic growth approach to be human development approach.  The change has change back human as the processor and to be the capital in development.  Purpose of this research is to find out the influence of economic growth, poverty, and regional expenditure partially and simultaneously to Human Development in Bali Province Period of 2005 – 2013.  Data type used is the secondary data by using panel data method.  Data analysis technique used the multiple linear regression.  Research result shows that partially the economic growth variable has positive and significant influence to human development index in Bali Province period of 2005 – 2013, partially the poverty index has significant negative influence to human development index in Bali Province period of 2005 – 2013, and partially the Regional Expenditure variable has positive and significant influence to human development index in Bali Province period of 2005 – 2013. Simultaneously the variables of economic growth, poverty, and Regional Expenditure have significant influence to human development index in Bali Province period of 2005 – 2013.
Keywords: Pertumbuhan Ekonomi, Kemiskinan, Belanja Daerah, Indeks Pembangunan Manusia